Orthodontic camouflage treatment of a hyperdivergent adolescent patient with anterior open bite and TMD: a case report - Yilin Jiang; Yajing Wang; Tianqi Wang; Dongqiao Liu; Chen Lin; Jing Wang; Cheng Zhi; Ziqian Qiu; Yuanfu Hou; Chunxiang Zhang (BMC, 2024)
Abstract Background In orthodontics, anterior open bite is a common malocclusion that recurs frequently. Because the causes of anterior open bite are so varied, medical professionals must create customized treatment programs for each patient based on their unique etiology. Through the lowering of the posterior teeth, closure of the anterior teeth gap, and cooperation with intermaxillary traction, the treatment plan outlined in this case study sought to achieve a stable occlusion. Case presentation This case report aims to describe an orthodontic camouflage treatment of a 15-year-old female patient with anterior open bite, arch width discrepancy and a history of temporomandibular joint disorder. The patient was treated with intermaxillary vertical elastics and the multiple edgewise arch wire (MEAW) approach. A satisfactory occlusion with a neutral molar relationship was attained after 29 months of orthodontic therapy. The condylography recording showed that this patient's occlusion tended to be more stable both before and after our treatment. The purpose of this case study is to provide an overview of an orthodontic camouflage treatment for a female patient, who had a history of temporomandibular joint disease, anterior open bite, and arch width disparity. Conclusions Our results demonstrated that more attention should be paid to levelling the occlusal plane, intrusion of the molars, decompression of temporomandibular joints and the etiology factors of malocclusion during the orthodontic period for those patients with anterior open bite.